A Japanese patient with a rare case of Streptobacillus moniliformis bacteremia. Issue 12 (December 2015) - Okamori, Satoshi; Nakano, Minoru; Nakamura, Mitsunobu; Takahashi, Eiji; Hasuike, Toshikazu; Nakamura, Yoshihiko; Aizawa, Daisuke
Abstract: Streptobacillus moniliformis is the etiological agent of rat-bite fever, a rare disease in Asia that is difficult to diagnose. We describe an elderly patient living in rat-infested conditions who presented with severe sepsis. He was successfully treated with meropenem, and blood culture revealed infection with S. moniliformis .